Pengendalian Internal, Budaya Organisasi, dan Kecenderungan Kecurangan Akuntansi di LPD Kabupaten Tabanan - Pratiwi, Ni Luh Gede Dandy Adi; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 30 No 11 (2020)DO - 10.24843/EJA.2020.v30.i11.p15, 2020)
This study aims to obtain empirical evidence regarding the influence of internal control and organizational culture on the tendency of accounting fraud in LPD Tabanan Regency. Tabanan Regency LPD was chosen in this study because of the phenomenon of fraud that occurred in several Tabanan Regency LPDs. Multiple linear regression is a data analysis technique used in this study. The results show that internal control and organizational culture negatively affect the tendency of accounting fraud in Tabanan Village Credit Institutions. This research can support the theory of fraud triangle as a theoretical implication of research. This research can provide input to improve internal control, organizational culture and reduce fraud committed by internal LPD parties as a practical research implication. Keywords: Tendency of Accounting Fraud; Internal Control; Organizational Culture.